An analysis of implicit knowledge to second language acquisition-SLA - Karnal, Adriana Riess (BELT - Brazilian English Language Teaching Journal, 2012)
This paper presents a historical overview concerning implicit knowledge and its relation to Second Language Acquisition (SLA). We contrast the symbolic and connectionist paradigms and how cognition is organized in each perspective. Moreover, we describe to what extent the interactionist perspective can be articulated under a cognitive model. The interface between explicit and implicit knowledge and the access problem are revisited as they are still the main tenets in the UG discussion. On the other hand, the connectionist point of view is oriented to the importance of internal mechanisms, such as memory and input processing. In spite of being two distinct approaches, they both recognize that most learning is implicit. The outcomes towards second language acquisition and teaching sketch how models should be built, that is, they ought to consider input, interaction and cognition.